Răspunsuri

2014-07-03T00:10:33+03:00
{[(67x-186)*4-45]*14+290}/500=1
[(67x - 186) × 4 - 45] × 14 + 290 = 500
[(67x - 186) × 4 - 45] × 14 = 500 - 290 = 210
(67x - 186) × 4 - 45 = 210 : 14 = 15
(67x - 186) × 4 = 15 + 45 = 60
67x - 186 = 60 ÷ 4 = 15
67x = 15 + 186 = 201
x = 201 ÷ 67
x = 3

1 5 1
Cel mai inteligent răspuns!
2014-07-03T00:43:02+03:00
[(67x-186)*4-45]*14+290=500*1=500

[(67x-186)*4-45]*14=500-290

(67x-186)*4-45=210:14

(67x-186)*4-45=15

(67x-186)*4=15+45

67x-186=60:4

67x-186=15

67x=15+186

67x=201

x=201:67

x=3
1 5 1